“Study of some doped and co-doped ceria and ceria/carbonate nanocomposite solid electrolytes for solid oxide fuel cells (SOFCs) - Jaiswal, Nandini (IIT (BHU), Varanasi, 2015)
Among the available renewable energy resources fuel cell is an emerging area for the production of electricity. The major drive to use fuel cells in place of conventional power systems is their efficiency, reliability, modularity, fuel flexibility, and environmental friendliness. There are so many types of fuel cells which are categorized based on the kind of electrolyte they employ. Among them, solid oxide fuel cells (SOFCs) have many advantages over others. SOFCs are clean and highly efficient energy conversion electrochemical devices. SOFCs have three main components namely an anode, an electrolyte and a cathode. The electrolyte plays a major role through which oxygen ions migrate constituting electric current. These should have high ionic conductivity, negligible electronic conductivity and very little porosity to avoid the crossover of the gases, stability in oxidizing and reducing atmosphere, thermally compatible with the anode and cathode and low cost. The present thesis is divided into nine chapters:
Keywords: Solid Oxide Fuel Cells, doped and co-doped ceria